Real Options and Discounted Cash Flow Analysis to Assess Strategic Investment Projects - Pivorienė Agnė (Economics and Business)
In today’s uncertain and highly competitive business environment, the difficulty to make strategic investment decisions is growing. The dominant discounted cash flow analysis requires the assumption of perfect certainty of project cash flows. However, under uncertainty traditional DCF approach falls short of providing adequate strategic decision support, and this situation demands new methods for investment evaluation. Real options approach (ROA) has shown the potential for valuation of strategic corporate investment decisions and managerial flexibility in situations of high uncertainty. Under ROA, projects are viewed as real options that can be valued using financial option pricing techniques. This framework allows their owner to keep investment options open and to benefit from the upside potential of an opportunity while controlling the downside risk. The main aim of this research is to investigate the feasibility of real options approach and traditional DCF analysis for assessment of strategic investment projects under environmental uncertainty.